2013
DOI: 10.1016/j.jvs.2012.10.101
|View full text |Cite
|
Sign up to set email alerts
|

Progress in management of malperfusion syndrome from type B dissections

Abstract: Malperfusion in any territory at the time of presentation in patients with type B dissections can be treated with endovascular intervention with acceptable outcomes. Opposed to branch vessel intervention alone, increased aortic intervention with regard to proximal coverage may signify more serious disease is associated with worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
1
32
1
Order By: Relevance
“…Cerebral ischemia may also be iatrogenic in nature. Coverage of the left subclavian artery (LSA) during TEVAR has been independently associated with increased rates of stroke and peri-operative mortality (48). These findings were corroborated in the STABLE trial, a prospective multicenter study involving 40 patients with complicated Type B dissections, in which all patients who suffered a post-operative stroke had required coverage of the LSA (41).…”
Section: Endovascular Therapy For Malperfusion Syndromementioning
confidence: 99%
“…Cerebral ischemia may also be iatrogenic in nature. Coverage of the left subclavian artery (LSA) during TEVAR has been independently associated with increased rates of stroke and peri-operative mortality (48). These findings were corroborated in the STABLE trial, a prospective multicenter study involving 40 patients with complicated Type B dissections, in which all patients who suffered a post-operative stroke had required coverage of the LSA (41).…”
Section: Endovascular Therapy For Malperfusion Syndromementioning
confidence: 99%
“…In our study, early mortality with TEVAR was 6.3%, and the main cause of in‐hospital mortality was malperfusion syndrome (mesenteric ischemia), increasing the risk of early death by 4.6×. Ryan et al reported a 30‐day mortality of 21.3% in patients with malperfusion syndrome, and ischemic territory was not independently associated with mortality . Other authors have reported 10.8% mortality .…”
Section: Discussionmentioning
confidence: 41%
“…Ryan et al reported a 30-day mortality of 21.3% in patients with malperfusion syndrome, and ischemic territory was not independently associated with mortality. 22 Other authors have reported 10.8% mortality. 20 Early mortality in our patients with malperfusion syndrome undergoing endovascular repair was 9.5%.…”
Section: Discussionmentioning
confidence: 95%
“…[3] It arises when the dissection compromises the blood flow, by either extrinsic compression of the true lumen by the false channel or an intimal flap occluding the orifice of a branch artery. [4] Another possible cause is intensive antihypertensive therapy for aortic dissection, which may worsen the perfusion of the visceral artery and enhance the ischemic visceral complication.…”
Section: Discussionmentioning
confidence: 99%
“…This complication sometimes requires surgical intervention, but it is associated with high morbidity and mortality. [3] Recently, endovascular revascularization has become the first treatment of choice for visceral malperfusion. [2] Generally, ischemia due to isolated celiac artery occlusion is rare because there are extensive collateral pathways for the mesenteric circulation.…”
Section: Discussionmentioning
confidence: 99%